(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article is focused on the investigation of identifying the motional dynamics of the evolutional development, disappearance or newly appeared semantic signs of the concept “Bakht” and “bakhtsizlik” (happiness and unhappiness) in the language by the help of the genesis and etymological analysis of “Bakht” (happiness) and its anti concept in Uzbek and English languages.